PENEGASAN KEBENARAN AGAMA TERHADAP SAINS - Fredy The (STT Bethel The Way, 2021)
Science and religion are interesting topics to discuss, because science and religion are often contradicted in the history of their development to date. The purpose of this research is to look at the position of science and religion by reaffirming the truth of religion, especially the Bible as the Word of God towards science. The research method used is a qualitative method with a systematic literature study using the approach of Ian G. Barbour and John F. Hought. Barbour's approach relates science and religion to four types of conflict, independent, dialogue, and integration relationships, while Hought uses four types of conflict, contrast, contact, and confirmation relationships. Based on Barbour and Hought's approach, it can be resulted that science has limitations so that religion must still be the umbrella of science, so that this confirms the truth of religion towards science. Conclusion of this research can be an enlightenment in the midst of different views regarding the creation of the universe according to the views of science and religion through the approach of Barbour and Hought who are scientists as well as theologians so that it can be seen more objectively. The Bible must still be believed to be the highest truth in the midst of the progress of scientific development. Keywords: Affirmation, Science, Truth, Religion